Implementasi Algoritma BERT untuk Question and Answer System Terkait Hadist dalam Bentuk Virtual Youtuber - Moch Arsyil Albany; Ichsan Taufik; Ichsan Budiman (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
In this digital era, the integration of Islamic teachings with advanced technology has become essential. This research focuses on developing an Islamic QnA system using Artificial Intelligence in the form of a Virtual YouTuber (VTuber). The system leverages the IndoBERT-SQuAD algorithm for Natural Language Processing, particularly in handling questions about hadiths. By employing prototype methodology, the system underwent stages of analysis, design, implementation, and evaluation. Confidence score and F1-score metrics were utilized to assess the system's performance. After contextual grouping, the model demonstrated significant improvement, achieving an F1-score of 0.96875. Despite these advancements, the system still faces challenges in providing accurate long-form answers. This research contributes to the application of technology in Islamic education, offering a practical solution for making hadith knowledge more accessible and appealing to the younger generation.